Utilization of Gasoline Fuel as an Alternative Fuel for LPG Substitution - Asril Mallombasang; Zuryati Djafar; Wahyu Haryadi Piarah (EPI International Journal of Engineering, 2020)
The subsidized gasoline conversion to LPG 3 kg in 2006 became the Indonesian Government’s policy to reduce reliance on fuel oil. The increasing LPG consumption and obstacle distribution have been the scarcity of the LPG in all regions of Indonesia. The gasoline fueled stove has overcome from the LPG scarcity. The purpose of this research was to compare the use of Gasoline types Pertalite and Pertamax with the use of LPG fuel. The research method was carried out by comparing the three types of fuel in the process of boiling 1 (one) litre of water using a gas stove, with several variations in pressure from 1.5 kPa to 2.5 kPa. The results showed that the highest fire temperature for Pertalite was 430 °C fuel, Pertamax 530 °C fuel and LPG 578 °C fuel. Fuel consumption for Pertalite 0,025 kg, Pertamax 0,027 kg and LPG 0,061 kg. The boiling time is 682 s for Pertalite, 669 s Pertamax and 503 s for LPG. The least compaction efficiency value occurs at 1.5 kPa pressure, for Pertalite 6,136 %, Pertamax 7,730 % and LPG 9,018 %. The higher the pressure, the greater the maturity efficiency, instead the fuel consumption and water boiling time are reduced. The cost used to boil water at Pertalite is Rp. 236,-; Pertamax Rp. 251,- and LPG is Rp. 309,-.